A q-Analogue of Rucinski-Voigt Numbers. (18th October 2012) - Corcino, Roberto B.; Montero, Charles B.
Abstract : A q -analogue of Rucinski-Voigt numbers is defined by means of a recurrence relation, and some properties including the orthogonality and inverse relations with the q -analogue of the limit of the differences of the generalized factorial are obtained.